QUALITY PARAMETERS IN NANOTECHNOLOGIC APPLICATIONS - Eker, Aysegul Akdogan; Kucukyildirim, Bedri Onur (UNIV MONTENENGRO, CENTER QUALITY, 2013)
Nanotechnology concept which has added a new dimension to our lives in recent years, is finding a place in every sector day by day. The combined effect of nanotechnology is almost equal to the industrial revolution of last 200 years and have is able to fill all developments in a few years. However this development should be taken under control. Otherwise unstoppable new structures will not ease life but will be a problem for humanity. For this purpose, the main parameters (from the start up stage of nano-technologic applications to the obtained product) should be checked. These parameters are actually not different than the adaptation of the classical quality indicators for nanotechnology applications. Especially it plays an important role in obtaining a uniform distribution and regarding the features of the end product in nano-technological ceramic and etc. applications. The most important problem faced in particles of that size is the accumulation they create. Another problem is the increasing friction force as size gets smaller. The friction force of a substance increases proportionally with the cube of its surface area. Another problem is surface tension. The increasing surface tension due to increasing surface area will cause the particles to attract and stick to each other. The structures aimed to be obtained are mostly complex and especially in upwards approach, it is thermodynamically very hard for the atoms to get into that order. Therefore in this announcement, we stated the quality parameters that will be taken into consideration in nano-technological applications and the methods for obtaining those parameters. The aim is to explain these parameters with all dimensions so that they will lead the way to the future nano-technological applications.
Keywords: nanotechnlogy; quality; parameters; Engineering